APPLICATIONS OF DIFFERENTIAL SUBORDINATION AND SUPERORDINATION - Ganesamoorthy, C.; Marikkannan, N.; Jeyaraman, M. P. (Journal of the Indonesian Mathematical Society, 2008)
In the present investigation we obtain asndwich theorems for certain subclass of analytic functions defined by convolution. Our results generalizes several well known results.DOI :Â http://dx.doi.org/10.22342/jims.14.1.62.47-56